The reality of epilepsy in primary care in Rio de Janeiro: the importance of educational projects for better patient care - Vanessa Cristina Colares Lessa; Marília Bezerra Magalhães Martins; Alexandra Seide Cardoso Vidal; Leonardo Alves Araujo; Isabella D'Andrea Meira (Arquivos de Neuro-Psiquiatria)
Background The Basic Health Unit (Unidade Básica de Saúde – UBS, in Portuguese) is the first point of contact in the public healthcare system for people with epilepsy. Primary care professionals need to appropriately diagnose, treat, and refer, if necessary, to tertiary services.